Globalization and the markups of European firms - Gábor Békés; Cecília Hornok; Balázs Muraközy (Kiel Institute for the World Economy (IfW), 2016)
We use a unique cross-section survey of manufacturing firms from four European countries (France, Germany, Italy, Spain) linked with balance sheet data to study the relationship between key aspects of globalization and firm-level markups. The main results are: (i) Exporting is positively correlated with markups; (ii) Importing intermediate inputs and outsourcing are also positively correlated with markups; (iii) Firms with affiliates have higher markups than other firms, while simply membership in a group or being foreign-owned seems to be less important; (iv) Perceived competition from low-cost markets is negatively correlated with markups; (v) Higher quality production and innovation, especially if it results in IP, has a strong positive relationship with markups; (vi) While these variables are correlated, they are significant in a joint model including all four groups, and 'fully globalized' firms tend to charge around 100% higher markups than non-globalized firms.
Keywords: D22; D24; F14; L11; L60; 330; markups; exporting; importing; FDI; innovation